On the diversity of the genus Pisione (Polychaeta, Pisionidae) along the Portuguese continental shelf, with a key to European species - Martins, Roberto; Martín, Guillermo San; Rodrigues, Ana Maria; Quintino, Victor (Zootaxa, 2012)
This work details the diversity and distribution of the genus Pisione Grube, 1857, Family Pisionidae Southern, 1914, on the Portuguese continental shelf. The study reports the first records for this region of the species P. guanche, P. inkoi and P. parapari, where previously P. remota was the only species reported. A detailed morphological study of the four species is presented, with a discussion of habitat preferences and biogeographic issues related to their distributional ranges. A total of 692 specimens were recorded at 48 sites. The four species coexist, with P. remota and P. parapari being the most abundant. A multivariate analysis based on morphological descriptors of 75 specimens showed a good separation of the four species. Pisione guanche and P. inkoi are characterized by a protruding notoacicula, longer in P. inkoi. These two species can be differentiated by the proportional length of the dorsal cirrus on parapodia 2 compared to parapodia 3, much longer in P. guanche, and by the number of distal teeth in the supra-acicular simple chaetae, bidentate in P. guanche and unidentate in P. inkoi. Of the four species, P. remota is the only one with an infra-acicular simple chaeta. The smallest intra-specific variability was found in P. parapari and the highest in P. guanche. The variability within species was much lower than the inter-specific variability which validated the four species of Pisione occurring in the Iberian Peninsula. This work set the meridional limit of P. inkoi and P. parapari, respectively in the western and the southern sector of the Portuguese continental shelf and the northern limit of P. guanche off the south margin of the Nazaré Canyon. Pisione guanche is here recorded for the first time in the Lusitanian biogeographic province, increasing to five the number of species known for European continental waters. A taxonomic key for the European Pisione species is given.